Pengalaman Memoderasi Pengaruh Idealisme dan Komitmen pada Keputusan Etis Konsultan Pajak di Wilayah Provinsi Bali - Wirakusuma, Made Gede (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 1 (2019)DO - 10.24843/JIAB.2019.v14.i01.p02, 2019)
Tax consultants are indispensable as associates of the Direktorat Jendral Pajak to help in raising awareness about the importance of taxpayer compliance. This study aims to determine the influence of experience on the relationship between idealism and professional commitment to ethical decision-making by tax consultants. The questionnaires were sent to the respondents/sample (members of Ikatan Konsultan Pajak Indonesia [IKPI]) of Bali Province. The sample was determined using the purposive sampling technique. Ninety questionnaires from 109 respondents working as tax consultants in Bali Province were collected as a pilot research, with a useable response rate of 84.1%. The results of the moderated regression analysis (MRA) analysis demonstrate that experience reinforces the positive influence of the relationship between idealism and ethical decisions of tax consultants, while it has no effect on the relationship between professional commitment and ethical decision-making by tax consultants in Bali Province. Keywords :  ethical decision, idealism, professional commitment, experience